Selective regulation of cellular cyclooxygenase by dexamethasone and endotoxin in mice. - Masferrer, J L (1990)
We have studied the effect of glucocorticoids administered in vivo on the activity and synthesis of the cyclooxygenase enzyme (COX) in mice treated with or without concurrent intravenous administration of LPS. Mouse peritoneal macrophages from LPS-treated animals showed a two to three fold increase in COX activity determined by the production of PGE2 and PGI2 after stimulation of the cells with exogenous arachidonate. Dexamethasone injected simultaneously with LPS, 12 h before killing of the animal and removal of the macrophages, completely blocked the LPS-induced increase COX activity in peritoneal macrophages. The regulation observed in COX activity by LPS and dexamethasone are due primarily to changes in COX mass as determined by immunoprecipitation of [35S]methionine endogenously labeled enzyme. In contrast, the COX present in the nonadherent cells and in renal medullary microsomes obtained from the same animals, showed no significant changes between treatments. These results indicate that LPS in vivo stimulates COX synthesis in the peritoneal macrophages but not in the kidney. The effect of dexamethasone to inhibit COX synthesis is selective to the LPS-induced enzyme.